Dissemination and Implementation of a Community Health Worker Intervention for Disparities in Palliative Care (DeCIDE PC): a study protocol for a hybrid type 1 randomized controlled trial. - Siddiqi, Amn.; Monton, Olivia.; Woods, Alison.; Masroor, Taleaa.; Fuller, Shannon.; Owczarzak, Jill.; Yenokyan, Gayane.; Cooper, Lisa A; Freund, Karen M; Smith, Thomas J; Kutner, Jean S; Colborn, Kathryn L; Joyner, Robert.; Elk, Ronit.; Johnston, Fabian M (Tufts University. Tisch Library., 2023)
Keywords: Palliative care, Cancer, Advanced cancer, Community health worker, CHW, Community, Health disparities, Racial disparities.; Springer Open.